Disciplining the Algorithm: Undergraduate TikTok Use and Creative Digital Agency at Victoria University, Kampala - Hakim Nkalubo; Augustine Osamor Ifelebuegu; Perpetua Cherukut (PT Agung Media Publisher, 2026)
As TikTok becomes a dominant global platform, concerns regarding its impact on higher education have increased. This study explores the intersection of TikTok usage, study habits, and academic performance among undergraduates at Victoria University, Kampala. It moves beyond the distraction critique to examine the role of Creative Digital Agency (CDA) in student engagement. A quantitative cross-sectional survey was conducted with a stratified random sample of 100 students across five faculties. Data were collected using the Palsane and Sharma Study Habits Inventory (PSSHI) and an Academic Performance Scale (APS). Analysis was performed in SPSS using descriptive statistics, Pearson correlation, and multiple linear regression. Findings show that TikTok use is widespread (65% regular users), yet intensive use is rare, with 58% spending less than one hour daily. No significant correlation was found between TikTok use and GPA (r = -0.095, p = 0.347) or study habits (r = 0.073, p = 0.471). Crucially, 51.3% of students utilized TikTok for academic learning, and 48.7% reported enhanced creativity. The results suggest that students at Victoria University effectively manage their digital behaviors through CDA, balancing entertainment with academic responsibilities. The study concludes that TikTok serves as a dual-purpose tool both recreational and instructional and does not inherently degrade academic performance. Universities should therefore focus on fostering digital agency rather than implementing restrictive social media policies.